Golgi retention of KIT in gastrointestinal stromal tumour cells is phospholipase D activity-dependent - Yuuki Obata; Miyuki Natsume; Isamu Shiina; Tsuyoshi Takahashi; Toshirou Nishida (Scientific Reports)
Abstract A constitutively active mutant of the receptor protein tyrosine kinase KIT is a major cause of gastrointestinal stromal tumours (GISTs). Recently, we discovered that, during biosynthetic transport, the KIT mutant (KITmut) is retained in the Golgi/trans-Golgi network (TGN), where it activates downstream molecules. This retention is dependent on the phospholipase Cγ2–protein kinase D2–PI4 kinase IIIβ (PLCγ2–PKD2–PI4KIIIβ) pathway, which KITmut activates at the Golgi/TGN. The activated cascade aberrantly recruits GGA1 and the γ-adaptin subunit of AP1, resulting in KITmut retention in the Golgi/TGN. However, the precise mechanisms, including the mediators and effectors of the pathway, remain unclear. In humans, the phosphatidic acid-generating enzymes, phospholipase D1 (PLD1) and PLD2 are known downstream proteins of PKD. In the presence of the PLD inhibitor CAY10594, KITmut is released from the Golgi/TGN and subsequently degraded in lysosomes, leading to signal inactivation. Knockdown experiments indicated that PLD2 plays a role in KITmut retention. KITmut activates PLD2 through PKD2, but not PI4KIIIβ, for Golgi/TGN retention. PLD activity is required for the association of γ-adaptin with GGA1. Therefore, the KIT–PLCγ2–PKD2 pathway separately activates PLD2 and PI4KIIIβ to recruit γ-adaptin and GGA1. Collectively, these results suggest that KITmut retention is dependent on the activation of the PLCγ2–PKD2–PLD2 cascade in GIST cells.